THE DEVELOPMENT OF THE EXPERIMENTAL MODEL OF PERIODONTITIS OF RATS IN CONDITIONS OF THE ACTION OF THE ANTAGONIST OF VITAMIN K - Nikolaeva, Anna (Journal of Education, Health and Sport, 2015)
The Aim of the study was the development of experimental model of the periodontitis at rats, similar to the human periodontitis by using the antagonist of the vitamin K - warfarin. Materials and methods. The experiment was conducted on 14 white male rats (2 groups), which were kept on a standard diet of the vivarium. The first group of rats was intact (6 animals). In the second group was simulated an experimental parodontitis in 8 rats that received the antagonist of the vitamin K - warfarin - the anticoagulant of indirect action in a dose of 1 mg / kg body weight of rats. The experiment lasted 50 days. Results and conclusions. Under the action of warfarin began the degradation of the MKM of periodontal, as evidenced by: the destruction of collagen of gum, downward trend of the GAG of periodontal bone structure, increasing the level of sialic acids in the blood serum. Antagonist caused an increased of resorption of alveolar bone; increased the activity of proinflammatory enzyme - acid phosphatasein in the gums and oral mucosa, and the MDA content in the alveolar bone. At the connective tissue of the lamina propria of the oral mucosa was noted the presence of moderately severe reactive changes under the influence of the antagonist of the vitamin K.